Basketball shooting performance and attentional strategies as a function of induced myopic blur - Lanham, S. E.; Robins, M. T. (World Congress of Performance Analysis of Sport IX, 2012)
Interestingly, previous research has indicated that the human movement system can tolerate a substantial level of myopic blur before performance is significantly affected (see Mann et al., 2010). However, the mechanisms underpinning this stabilisation of performance are yet to be identified, a point acknowledged by Mann and co-workers (2007) as a fruitful line of future scientific enquiry. Two potential mechanisms have been theorised; (1) allocation of additional attentional resources, and (2) focus of attention. Therefore, the purpose of this study was to discern which mechanism best explains performance changes with induced myopic blur. Eight skilled basketball players provided voluntary written informed consent to participate and completed 20 free throws under each of four, counterbalanced visual conditions. All participants met stringent inclusion criteria in terms of task expertise and habitual vision. The four vision conditions were plano, +1.00D, +2.00D and +3.00D causing visual acuities of approximately 6/4-6/6, 6/6-6/12, 6/18-6/24 and 6/60 respectively. Shooting performance was assessed using a 1-8 scale and attentional demands were quantified using a vocal reaction time test. In addition, each participant completed a focus of attention questionnaire after each visual condition. Statistical differences for each dependent variable were examined using a repeated measures analysis of variance (p.</= 0.05). A significant decrease in shooting performance was observed between the plano and +3.00D conditions (p=0.03). There was no significant difference in reaction time or focus of attention with respect to myopic blur (p>0.05). However, due to large within group variance a multiple single-individual level of analysis was conducted and revealed; (1) a strong positive relationship between percentage change in reaction time and performance between the plano and +3.00D conditions (r=0.7, p=0.05) and (2) participants self-selected different foci of attention e.g. follow through movement (internal focus), starting position (internal focus), or success of the shot (external focus). Collectively, these results provide the first line of evidence to suggest that stabilisation of performance with induced myopic blur can be achieved by allocating additional attentional resources to the task. Moreover, the adoption of an external focus of attention may further facilitate this stabilisation because participants did not inherently self-select this focus of attention during the performance trials. Therefore, these results highlight the potential utility of attentional training programmes.